2010
DOI: 10.1016/j.bcp.2010.07.043
|View full text |Cite
|
Sign up to set email alerts
|

Tocotrienols, the vitamin E of the 21st century: Its potential against cancer and other chronic diseases

Abstract: Initially discovered in 1938 as a "fertility factor," vitamin E now refers to eight different isoforms that belong to two categories, four saturated analogues (α, β, γ, and δ) called tocopherols and four unsaturated analogues referred to as tocotrienols. While the tocopherols have been investigated extensively, little is known about the tocotrienols. Very limited studies suggest that both the molecular and therapeutic targets of the tocotrienols are distinct from those of the tocopherols. For instance, suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
401
3
15

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 501 publications
(421 citation statements)
references
References 226 publications
(249 reference statements)
2
401
3
15
Order By: Relevance
“…tocos) are fat-soluble vitamins and are generically regarded as vitamin E, for which the antioxidant properties are well studied. Vitamin E is thought to prevent atherosclerosis, protect against coronary disease, and prevent neurons from oxidative stress and the development of AD and possibly cancers (Aggarwal, Sundaram, Prasad, & Kannappan, 2010;Rong et al, 2013).…”
Section: Cvds Oxidative Stress Alzheimer's and Cancermentioning
confidence: 99%
“…tocos) are fat-soluble vitamins and are generically regarded as vitamin E, for which the antioxidant properties are well studied. Vitamin E is thought to prevent atherosclerosis, protect against coronary disease, and prevent neurons from oxidative stress and the development of AD and possibly cancers (Aggarwal, Sundaram, Prasad, & Kannappan, 2010;Rong et al, 2013).…”
Section: Cvds Oxidative Stress Alzheimer's and Cancermentioning
confidence: 99%
“…Le terme generique vitamine E regroupe deux grands groupes de molecules : les tocopherols et les tocotrienols, comprenant chacun 4 vitameres a, b, g et d (Jensen et Lauridsen, 2007 ;Aggarwal et al, 2010 ;Brigelius-Flohe, 2009 ;Azzi, 2007 ;Traber et Atkinson, 2007). Leurs structures chimiques se composent d'un cycle chromanol mono-, di-, ou trimethyle auquel est rattachee une chaîne laterale a 16 atomes de carbone, de structure isoprenique (figure 1).…”
Section: Quelques Generalitesunclassified
“…Among the vitamin E isomers, a-tocopherol has the highest bioavailability as it is preferentially absorbed by the body. 19,20 This is the reason why a-tocopherol is the most studied and widely available vitamin E. 21 aTocopherol has also been claimed to be the most important lipid-soluble anti-oxidant, and that it protects membranes from oxidation by reacting with lipid radicals produced during the lipid peroxidation chain reaction. 22,23 Studies have shown mixed results on the effects of a-tocopherol on fracture healing but all these studies were conducted in normal bone.…”
mentioning
confidence: 99%